PENETAPAN USIA KEDEWASAAN DALAM SISTEM HUKUM DI INDONESIA - Ruzaipah, Ruzaipah; Manan, Abdul; A’yun, Qurrota A’yun (Mitsaqan Ghalizan, 2021)
A person's age limit is said to be regulated in statutory regulations. But in the case of determining the age limit of maturity is still very diverse and has not yet reached a common ground on the certainty at what age a person can be said to be an adult, the age limit for adults between the rules of one another still does not show similarity, giving rise to ambiguity in the determination of a person's age of maturity, which ultimately will result in the validity of someone in carrying out the action or legal action taken. Departing from these problems, this paper aims to look at how a person's age is determined by Islamic law and the legal system in force in Indonesia. Islamic law limits the maturity of a person characterized by wet dreams in men and menstruation in women, while Positive law is 18 years or has been married. The legality of legal actions of persons who are not yet mature in Islamic law is legal, whereas in positive law in civil law it is also considered legitimate as long as there is no claim.